2023
DOI: 10.3390/v15020334
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp2 Contributes to Inflammation by Activating NF-κB

Abstract: COVID-19 is associated with robust inflammation and partially impaired antiviral responses. The modulation of inflammatory gene expression by SARS-CoV-2 is not completely understood. In this study, we characterized the inflammatory and antiviral responses mounted during SARS-CoV-2 infection. K18-hACE2 mice were infected with a Wuhan-like strain of SARS-CoV-2, and the transcriptional and translational expression interferons (IFNs), cytokines, and chemokines were analyzed in mouse lung homogenates. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The S protein activates the canonical pathway controlling the NLRP3 inflammasome in both mononuclear cells and neutrophils in patients [ 7 ]. The non-structural protein (NSP)2 triggers the transcription of NLRP3 protein through NF-κB signaling [ 8 ]. The N protein of SARS-CoV-2 directly binds to NLRP3 and triggers the formation of the NLRP3 inflammasome, thereby inducing excessive inflammatory response, acute lung injury, and accelerated sepsis-induced death [ 9 ].…”
Section: Nlrp3 Inflammasome and Sars-cov-2mentioning
confidence: 99%
“…The S protein activates the canonical pathway controlling the NLRP3 inflammasome in both mononuclear cells and neutrophils in patients [ 7 ]. The non-structural protein (NSP)2 triggers the transcription of NLRP3 protein through NF-κB signaling [ 8 ]. The N protein of SARS-CoV-2 directly binds to NLRP3 and triggers the formation of the NLRP3 inflammasome, thereby inducing excessive inflammatory response, acute lung injury, and accelerated sepsis-induced death [ 9 ].…”
Section: Nlrp3 Inflammasome and Sars-cov-2mentioning
confidence: 99%
“…Plenty of cytokines and inflammatory indicators, like TNF-α, CRP, IL-1, and IL-6, have been related to the development of CKD ( 40 ). These inflammatory factors are closely linked to the triggering of the nuclear factor-κB (NF-κB) cascade ( 41 ). Such a pathway would induce mitochondrial dysfunction and increased amounts of reactive oxygen species (ROS) ( 42 , 43 ), and NF-κB may cause an inflammatory cytokine feedback loop that might maintain kidney inflammation ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both SARS-CoV and SARS-CoV-2 NSP1 proteins can inhibit IFN response. However, Lacasse et al (65) discovered that NSP2 of SARS-CoV-2 can activate the NF-κB pathway and the IFNβ promoter. They also found that NSP2 of SARS-CoV-2 partially counteracts the IFN inhibitory activity of NSP1.…”
Section: Discussionmentioning
confidence: 99%